Another perspective of strain selection based on functional traits: construction and evaluation of a key complex index for endangered species plantation - Xu, Jinshi; Han, Biao; Liu, Dan; Pang, Jintao; Guo, Huixin; Zhou, Xiang; Zhang, Ping (Frontiers in Plant Science, 2025)
IntroductionEndangered species can achieve population growth through utilization. Juglans mandshurica is an endangered species, which can be used in gardens and street trees. To avoid population degradation caused by long-term nursery cultivation, we need to introduce high-quality wild sources of germplasm for hybridization. In the past, when the selection of strains was carried out, attention was often paid to the performance of different traits of each strain. The strains with advantages in many more traits were selected as the target. In this paper, we proposed that excellent strains should be selected based on the needs of managers.MethodsWe constructed a complex index composed of insect resistance and growth amount, which was concerned by plantation managers, for the selection of excellent strains. Its availability was confirmed as well. We cultivated 16 wild-sourced J. mandshurica strains in a homogeneous garden and carried out experiments for 3 years. We measured 28 functional traits. Through collinearity diagnostics, 15 functional traits in 4 dimensions (morphology, leaf economy, stoichiometry and reproduction) were selected for analysis and construction of complex index. The influence of environmental factors on traits was excluded by comparing the trait matrix calculated based on Euclidean distance with the geographical distance matrix.ResultsExcellent strains (No. 15 from Dazeshan) selected based on the key complex index may not be outstanding in each trait, but have a more balanced performance among the trade-offs of trait combinations. We also explored the visualization of this key complex index by correlating with leaf carbon content (its ecologically relevant trait), so as to realize rapid and early selection of J. mandshurica strains by using LCC (an easily measurable trait).DiscussionTo construct key complex index, appropriate functional traits should be selected according to the needs of managers or different species. The measurable traits with clear ecological links with complex index should be selected as "agents" to realize visualization of complex index.